2006
DOI: 10.1007/s00296-006-0268-3
|View full text |Cite
|
Sign up to set email alerts
|

Lupus patients with pulmonary involvement have a pro-inflammatory cytokines profile

Abstract: Lupus patients with pulmonary involvement have a stronger pro-inflammatory cytokine bias than those without pulmonary involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
0
20
1
4
Order By: Relevance
“…The significant positive correlation between serum TNF-α and bFGF levels seen in the whole patient group and HRCT-negative subjects and the lack of similar correlation in HRCT-positive patients might support such hypothesis in the light of the role of bFGF in fibrosis [15]. The results concerning the level of TNF-α in our study differ from the earlier ones obtained by other authors who observed increased serum level of this factor in SLE patients [16,17] especially in SLE subjects with pulmonary involvement [17]. The demonstrated differences could be partially explained by lower disease activity in our patients (calculated on the day of blood sampling SLEDAI score was <10 or slightly higher) [18].…”
Section: Discussioncontrasting
confidence: 90%
“…The significant positive correlation between serum TNF-α and bFGF levels seen in the whole patient group and HRCT-negative subjects and the lack of similar correlation in HRCT-positive patients might support such hypothesis in the light of the role of bFGF in fibrosis [15]. The results concerning the level of TNF-α in our study differ from the earlier ones obtained by other authors who observed increased serum level of this factor in SLE patients [16,17] especially in SLE subjects with pulmonary involvement [17]. The demonstrated differences could be partially explained by lower disease activity in our patients (calculated on the day of blood sampling SLEDAI score was <10 or slightly higher) [18].…”
Section: Discussioncontrasting
confidence: 90%
“…12 In terms of lung involvement only a few studies are available, suggesting that some of these markers can be elevated in blood and exhaled breath condensate of SLE patients with pulmonary manifestations. 13,14 Previous studies reported interleukin (IL)-6, IL-8, interferon-g (INF-g) and tumor necrosis factor-a (TNF-a) as possible markers for pulmonary manifestation in SLE patients. 13,15 However, these markers are not specific enough to identify the pulmonary manifestations, as their levels are elevated in many pathophysiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Previous studies reported interleukin (IL)-6, IL-8, interferon-g (INF-g) and tumor necrosis factor-a (TNF-a) as possible markers for pulmonary manifestation in SLE patients. 13,15 However, these markers are not specific enough to identify the pulmonary manifestations, as their levels are elevated in many pathophysiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Mutairi et al 13 reported that proinflammatory cytokines (tumor necrosis factor, interferon-γ, IL-8) were more prevalent in the serum of patients with pulmonary involvement compared with those without pulmonary manifestations. However, the serum levels of IL-10 were similar in the pulmonary and nonpulmonary phenotypes.…”
Section: Methodsmentioning
confidence: 99%